2010
DOI: 10.1176/appi.ajp.2010.09111619
|View full text |Cite
|
Sign up to set email alerts
|

Altering the Trajectory of Anxiety in At-Risk Young Children

Abstract: This brief, inexpensive intervention shows promise in potentially altering the trajectory of anxiety and related disorders in young inhibited children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
170
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 234 publications
(172 citation statements)
references
References 29 publications
0
170
0
2
Order By: Relevance
“…5,12 These rates are, however, consistent with other research with preschool-aged inhibited children. 34 This may be due to the fact that anxiety was assessed at the same time as the participants were selected as being BI. Over time, some BI children become more confident and no longer meet the definition for BI.…”
Section: 16mentioning
confidence: 99%
“…5,12 These rates are, however, consistent with other research with preschool-aged inhibited children. 34 This may be due to the fact that anxiety was assessed at the same time as the participants were selected as being BI. Over time, some BI children become more confident and no longer meet the definition for BI.…”
Section: 16mentioning
confidence: 99%
“…Thus, the number of potential mechanisms and sites accountable for the dysregulation is vast (Pathak & Perry, 2006). Likewise, the environmental factors and components of social and physical threat concerns involved in childhood anxiety are hard to identify (Rapee, Kennedy, Ingram, Edwards, & Sweeney, 2010), particularly in the case of childhood TA (Nyroos et al, 2015a). Anxiety disorders belong to the most prevalent types of psychopathology during childhood occurring in magnitudes up to 10-15%, and showing an increased developmental trend (Kozina, 2014).…”
Section: Phenomenonmentioning
confidence: 99%
“…188 Although scarce, there is promising evidence that treatments based on existing therapies (CBT, parental training, and pharmacotherapy), adapted to atrisk populations, i.e., highly symptomatic children, but still not meeting criteria for the diagnosis of anxiety disorders, or children with first-degree relatives diagnosed with anxiety disorders, result in preventing and reducing the severity of these disorders. 189 This is a general overview about pediatric anxiety disorders. More specific and comprehensive reviews about the following topics can be found in the literature: prevalence, 15,[18][19][20] behavioral inhibition, [190][191][192] behavioral genetics, 48,52 genetics, 55,56,193,194 gene vs. environment interplay, 52,70 pathophysiology, 31,71 neural substrates, 71 normal development of fears, 195 psychopharmacological treatment, [196][197][198] and CBT.…”
Section: Preschool Children Treatment and Preventionmentioning
confidence: 99%